2006
DOI: 10.1016/j.jvs.2006.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Residual varicose veins below the knee after varicose vein surgery are not related to incompetent perforating veins

Abstract: This study shows that reflux in the GSV below knee level after the short-stripping procedure persists in all below-knee GSV branches. Approximately 20% of patients with visible varicose veins in the GSV area below the knee level will have visible varicose veins in this area 6 months after the short-strip procedure. These clinical and ultrasonic residual varicose veins are not significantly related to the presence of preoperative IPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…This policy has been in use in the participating hospitals for years because it was found that most patients with varicose veins did not need extra interventions 2 to 3 months after stripping the GSV. This was also confirmed by van Neer et al 21 All patients were given subdermal low-molecularweight heparin injections (2500 U, Dalteparin, Pfizer) preoperatively and for 1 day postoperatively.…”
Section: Methodssupporting
confidence: 59%
“…This policy has been in use in the participating hospitals for years because it was found that most patients with varicose veins did not need extra interventions 2 to 3 months after stripping the GSV. This was also confirmed by van Neer et al 21 All patients were given subdermal low-molecularweight heparin injections (2500 U, Dalteparin, Pfizer) preoperatively and for 1 day postoperatively.…”
Section: Methodssupporting
confidence: 59%
“…Our past experience and results of previous studies comparing the results of three different surgical techniques (complete stripping with HL, partial above‐knee stripping with HL, and HL alone) have shown that the best recurrence rate, best improvement in CEAP class, and best event‐free survival rates are achieved using complete stripping with HL 18,19 . The rate of residual reflux and recurrence after partial stripping can reach up to 20%, and this complication is found more often with patent below‐knee saphenous veins than with IPVs undetected preoperatively 20 . Given that these techniques are theoretically equivalent to stripping with low ligation of the proximal saphenous vein, it is not wise or completely true to claim that their recurrence rates and effectiveness are better than those of complete stripping with HL.…”
Section: Discussionmentioning
confidence: 99%
“…The predictors of postoperative symptom recurrence and clinical and Doppler examination findings depend on the preoperative and demographic characteristics of individual patients. The clearly demonstrated and suggested advantages of this hybrid technique (i.e., ligation plus foam sclerotherapy) can be summarized as follows: Doppler is not required; preoperative and postoperative hospitalization is not needed (as it is in surgical therapy); general or spinal anesthesia is not needed; potential complications and hazards of invasive procedures are avoided; it is a technique that can be used safely in older patients and in patients who are unable to undergo general or regional anesthesia; complete division of the SFJ and side branches can be achieved, which is not possible with EVLT or RF; the risk of the recurrence is minimized; and by sclerosing the saphenous vein below the knee, various proliferations originating from this level can be minimized 20 . Ligation plus foam sclerotherapy not only has potential to achieve the ideal long‐term follow‐up results seen with surgical stripping, but also makes it possible to obtain the ideal cosmetic results, postoperative comfort, and minimum complication rates of other non‐invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had participated in an earlier study. 6 Consecutive ambulatory patients who presented to the dermatology or surgery department with untreated varicose veins (no conservative treatment and no intervention of any kind previously) were asked to enroll in the study. Patients with varicose veins and reflux of the saphenofemoral junction and reflux of at least the upper leg part of the GSV were included.…”
Section: Methodsmentioning
confidence: 99%
“…Although persistent reflux in the below knee GSV has never been a major study objective, a few studies have revealed that a significant number of these patients have a persistent reflux in the below knee GSV from 2 months up to 2 years after this type of surgery. [3][4][5][6] This study was designed to investigate the occurrence of persistent reflux of the GSV below the knee after a short stripping procedure and to investigate the possible role of incompetent perforating veins (IPVs) on this reflux.…”
mentioning
confidence: 99%